Plant extract as complementary treatments in the wound healing process of diabetic foot - Mejía-Benavides, Jorge Emmanuel (2023)
Diabetic foot ulcers are microvascular lesions considered one of the most serious complication of people with diabetes, by not having sufficient caution and care they can evolve into ulcers with difficult and slow healing, coupled with all existing pharmacological treatments, people of indigenous communities complement the treatments by using Traditional Medicine (TM) with adjuvant treatments based on plant extracts that help the wound healing process. The objective was to know the use of Aloe vera, honney, Calotropis procera, Caléndula officinalis, Plectranthus amboinicus y Centella asiática, Jatropha multífida, Phellodendri, Annona muricata L, however, most localized clinical studies are performed in rodents and in-vitro. This is due to the methodologies established to determine the safety and efficacy of use in humans and in this way, through the multidisciplinary health team, collaborate with the Traditional Medicine Strategy 2014-2023 proposed by the World Health Organization (WHO) in addition to respecting the beliefs, values and lifestyles of people with cultural identity.